Decreasing polar-structure size: Achieving superior energy storage properties and temperature stability in Na0.5Bi0.5TiO3-based ceramics for low electric field and high-temperature applications. Issue 12 (September 2021) - Zhang, Lei; Pu, Yongping; Chen, Min; Zhuo, Fangping; Dietz, Christian; Frömling, Till
Abstract: It is a grand challenge to achieve high energy density (W) and efficiency (η) simultaneously under a low electric field (LE) to obtain new high energy storage capacitors. Similar to anti-ferroelectrics, the (1- x )NBT- x BaMg1/3 Nb2/3 O3 relaxor material exhibits a non-linear dependence on electric field, which is caused by a reversible field-induced phase transition. This leads to high W (2.37 J/cm 3 ) and η (81.5 %) under a LE of 155 kV/cm, which makes it superior to other bulk ceramics. Combining large polarizability of Ba 2+ in A-site and local structural heterogeneity on the B-site by Mg1/3 Nb2/3 4+, enhanced relaxor behavior and decreased polar-structure size were induced in (1- x )NBT- x BaMg1/3 Nb2/3 O3 ceramics. The permittivity, nevertheless, stays high at ∼2273±15 %. Furthermore, the electrical properties become stable in a wide temperature range from 44−396 °C for the sample with x =0.15. In addition, high current density/CD (450 A/cm 2 ), power density/PD (23 MW/cm 3 ) and discharge density/WD (0.57 J/cm 3 ) were realized tested with pulse discharge testing. Our work will provide a development guidance for dielectric energy storage ceramics at low field and high fields with excellent temperature stability.